Single-Cell Analysis Revealed the Role of CD8+ Effector T Cells in Preventing Cardioprotective Macrophage Differentiation in the Early Phase of Heart Failure - Komai, Kyoko; Ito, Minako; Nomura, Seitaro; Shichino, Shigeyuki; Katoh, Manami; Yamada, Shintaro; Ko, Toshiyuki; Iizuka-Koga, Mana; Nakatsukasa, Hiroko; Yoshimura, Akihiko (Frontiers in Immunology, 2021)
Heart failure is a complex clinical syndrome characterized by insufficient cardiac function. Heart-resident and infiltrated macrophages have been shown to play important roles in the cardiac remodeling that occurs in response to cardiac pressure overload. However, the possible roles of T cells in this process, on the other hand, have not been well characterized. Here we show that T cell depletion conferred late-stage heart protection but induced cardioprotective hypertrophy at an early stage of heart failure caused by cardiac pressure overload. Single-cell RNA sequencing analysis revealed that CD8+T cell depletion induced cardioprotective hypertrophy characterized with the expression of mitochondrial genes and growth factor receptor genes. CD8+T cells regulated the conversion of both cardiac-resident macrophages and infiltrated macrophages into cardioprotective macrophages expressing growth factor genes such as Areg, Osm, and Igf1, which have been shown to be essential for the myocardial adaptive response after cardiac pressure overload. Our results demonstrate a dynamic interplay between cardiac CD8+T cells and macrophages that is necessary for adaptation to cardiac stress, highlighting the homeostatic functions of resident and infiltrated macrophages in the heart.